Efficacy and Safety of 12-week Monotherapy With Once Daily 5 mg Tadalafil for Lower Urinary Tract Symptoms of Benign Prostatic Hyperplasia: Evidence-based Analysis - Cui, Jianwei; Cao, Dehong; Bai, Yunjin; Wang, Jiahao; Yin, Shan; Wei, Wuran; Xiao, Yunfei; Wang, Jia; Wei, Qiang (Frontiers in Medicine, 2021)
Background: Tadalafil has been approved for the treatment of benign prostatic hyperplasia for nearly 10 years. However, there are insufficient evidence-based studies of the efficacy and safety of tadalafil in treating lower urinary tract symptoms of benign prostatic hyperplasia(LUTS/BPH). Objective：To evaluate therapeutic effect and clinical safety of tadalafil monotherapy (5 mg once daily for 12 weeks) for LUTS/BPH. Methods: 13 studies (15 random clinical trials[RCTs]) were extracted from the following databases: PubMed, Cochrane Central Register of Controlled Trials, Embase, and Web of Science for the period up to July 2021. The quality of the included RCTs was evaluated independently by two authors, who respectively extracted data according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses(PRISMA) principles. Conflicts were settled by discussion with two third senior authors. All data analyses were conducted by the Review Manager, version 5. 4. Results: Regarding efficacy, 12-week trials indicated that 5 mg once daily tadalafil showed a significantly lower and, consequently, better total International Prostate Symptom Score (IPSS) than the placebo did (mean difference[MD]: -1.97, 95% confidence interval[CI]: -2.24 to -1.70; P<0.00001). In addition, significant differences were found between the tadalafil regimen and the placebo in the IPSS voiding sub-score(MD: -1.30, 95% CI: -1.48 to -1.11; P <0.00001), the IPSS storage sub-score(MD: -0.70, 95% CI: -0.82 to -0.58; P<0.00001), the IPSS quality of life(IPSS QoL)(MD: -0.29, 95%CI: -0.35 to -0.22; P<0.00001), and BPH Impact Index(BII)(MD: -0.58, 95%CI: -0.76 to -0.40; P<0.00001). The safety analysis did not show a significant difference in serious adverse events(SAEs) between the two groups (risk ratio[RR]: 1.27, 95%CI: 0.80 to 2.01; P=0.31), although that adverse events(AEs) occurred at a higher incidence in the tadalafil group than in the placebo. Conclusions: The present study demonstrates that once daily 5 mg tadalafil is a potentially effective and safe treatment choice with excellent tolerability for patients with LUTS/BPH.